(untitled) (Al-Academy, 2024)
The concept of clarity and readability of the written texts is an important goal in order to convey the communication idea to the receiver easily; the written texts have special significance because it is the most effective way to fulfill this idea as well as to achieve the aesthetic dimension of the written material, and clarity in the written texts is a prerequisite for reading, and readability is the speed of the optical reading of the written form, as the letters design plays a key role in facilitating the readability of the texts, and thus, it is necessitated to take care of these texts and studied them thoroughly in terms of shape for easy to read, and thus to understand the implications of the texts.For that reason, the researchers have identified the problem of their research the following question?:Are the clarity and readability fulfilled in the commercials designsThe importance of the current research is shown in enriching the cognitive side of the clarity and readability for those who involved in the design field in commercials as well as opening scientific horizons towards the development of ideas presented in commercials designs.As for the objective of this research, it lies in the detection of the clarity and readability concept of the commercials designs.The research limits of the commercials included the physical and objective limits as well as the spatial limits of Arab commercial ads and time limits in 2009, and that what was included in the first chapter.The second chapter covers the theoretical scope which included (the concept of clarity, readability and the spatial organizing variables of the written texts and formal elements in the commercials).The third chapter is devoted to the research procedure, where the researchers followed the descriptive content as a method to analyze the content for the purpose of monitoring the phenomena.The unit of analysis is identified for the reason that it bears an integrated communication idea in which ideas can be elicited through the analysis and thus 24 units were formed as samples of the research community in which (3) samples have been selected using the non-probabilistic intentionality manner of the total community.The researchers have reached in the fourth chapter to scientific findings and conclusions in which objectives set were achieved. These results include the following1.The reading clarity in terms of implementation, use, alignment, spacing, and choosing of letters were not suitable due to the decrease in font size compared to the size of the advertisement in the advertising texts as in the sample (1) 2.The written texts are a design necessity because it is complementary to the images to interpret and explain them because the advertisement needs precision to be interpreted and to show its design idea content, as in the sample (1), (3)3.The written texts are an influential factor in achieving clarity and readability and the ability to absorb the formal employment as in the sample (2)4.Spacing between lines and characters in the written texts were not carefully considered which leads to lack of readability and clarity as in the samples (1), (3).